The effect of knee resizing illusions on pain and swelling in symptomatic knee osteoarthritis: a case report - MacIntyre, Erin (Pain Rep, 2019)
INTRODUCTION: Resizing illusions that manipulate perceived body size are analgesic in some chronic pain conditions. Little is known whether such illusions may also alter other physiological features, such as swelling. OBJECTIVES: To determine the effects of a knee resizing illusion on knee pain and swelling in symptomatic osteoarthritis. METHODS: This case study was extracted from a larger study evaluating the analgesic effects of resizing illusions in people with knee osteoarthritis. A mediated reality system (alters real-time video) was used to provide resizing “stretch” and “shrink” illusions of the knee. Knee pain intensity (0–100 numerical rating scale) was measured before and after illusion and after sustained (3 minutes) and repeated (n = 10) illusions. In this case study, knee swelling (leg circumference below, at, and above the knee) was also measured. RESULTS: The 55-year-old male participant reported a long history of episodic knee pain and swelling that was subsequently diagnosed as severe osteoarthritis in 2013. In the first testing session, the participant experienced an increase in pain with the shrink illusion and a decrease in pain with stretch illusion. A noticeable increase in knee swelling was also observed. Thus, in sessions 2/3, swelling was also assessed. The stretch illusion decreased pain to the largest extent, but resulted in increased knee swelling. Repeated and sustained stretch illusions had cumulative analgesic effects but resulted in cumulative increases in swelling. While the shrink illusion increased pain, sustained (∼10 minutes) visual minification of the entire knee and leg reduced both pain and swelling. CONCLUSION: Our case report suggests that both pain and swelling may be modifiable by altering body-relevant sensory input in symptomatic knee osteoarthritis.